A Tangible Spherical Proxy for Object Manipulation in Augmented Reality - Englmeier, David; Dorner, Julia; Butz, Andreas; Hollerer, Tobias (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2020)
In this paper, we explore how a familiarly shaped object can serve as a physical proxy to manipulate virtual objects in Augmented Reality (AR) environments. Using the example of a tangible, handheld sphere, we demonstrate how irregularly shaped virtual objects can be selected, transformed, and released. After a brief description of the implementation of the tangible proxy, we present a buttonless interaction technique suited to the characteristics of the sphere. In a user study (N = 30), we compare our approach with three different controller-based methods that increasingly rely on physical buttons. As a use case, we focused on an alignment task that had to be completed in mid-air as well as on a flat surface. Results show that our concept has advantages over two of the controller-based methods regarding task completion time and user ratings. Our findings inform research on integrating tangible interaction into AR experiences.